2022
DOI: 10.1111/apt.16832
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to endoscopic surveillance for advanced lesions and colorectal cancer in inflammatory bowel disease: an AEG and GETECCU collaborative cohort study

Abstract: Summary Background and Aims Patients with colonic inflammatory bowel disease (IBD) have a high risk of colorectal cancer (CRC). Current guidelines recommend endoscopic surveillance, yet epidemiological studies show poor compliance. The aims of our study were to analyse adherence to endoscopic surveillance, its impact on advanced colorectal lesions, and risk factors of non‐adherence. Methods A retrospective multicentre study of IBD patients with criteria for CRC surveillance, diagnosed between 2005 and 2008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Among them, 13%, 34% and 39% of patients did not perform or delayed follow-up procedures, respectively ( p < 0.001). Groups at higher risk of CRC are associated with lower adherence [ 126 ]. The possible reasons mentioned may be transportation, finances and discomfort with the procedure or bowel preparation as barriers to endoscopic surveillance adherence [ 127 ].…”
Section: Surveillance For Crc In Ucmentioning
confidence: 99%
“…Among them, 13%, 34% and 39% of patients did not perform or delayed follow-up procedures, respectively ( p < 0.001). Groups at higher risk of CRC are associated with lower adherence [ 126 ]. The possible reasons mentioned may be transportation, finances and discomfort with the procedure or bowel preparation as barriers to endoscopic surveillance adherence [ 127 ].…”
Section: Surveillance For Crc In Ucmentioning
confidence: 99%
“…A large Spanish multicenter study reported adherence to the European Crohn's and Colitis Organisation surveillance guidelines for 43% for first surveillance colonoscopy and a total adherence of only 27% of their patients. 27 Chromoendoscopy was performed in 25% of initial procedures and 38% of subsequent surveillance procedures. A representative IBD cohort based on a sequential clinical attendance over a 6-month period at a Canadian center demonstrated adherence to surveillance guidelines of 76% and 82% for UC and colonic CD, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that has previously been identified is clinicians not being aware of surveillance recommendations or not organizing surveillance procedures. 27 All clinicians involved in this study had knowledge and access to the Australian guidelines for IBD surveillance. These guidelines were included as part of the national clinical practice guidelines for the prevention, early detection, and management of CRC, created by the Cancer Council Australia and approved by the National Health and Medical Research Council of Australia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations